A pooled CRISPR screen identifies the Tα2 enhancer element as a driver of TRA expression in a subset of mature human T lymphocytes - Schönberg, Pascal Y.; Muñoz-Ovalle, Ángela; Paszkowski-Rogacz, Maciej; Crespo, Eugenia; Sürün, Duran; Feldmann, Anja; Buchholz, Frank (Frontiers in Immunology, 2025)
The T cell receptor (TCR) is crucial for immune responses and represents a pivotal therapeutic target for CAR T cell therapies. However, which enhancer elements drive the constitutive expression of the TCRα chain in mature, peripheral T cells has not been well defined. Earlier work has suggested that enhancer alpha is inactive in mature peripheral T cells and that an alternative enhancer element in the 5’ J region was driving TRA expression, while more recent findings indicated the opposite. Here, we applied a pooled CRISPR screen to probe a large genomic region proximal to the human TRA gene for the presence of regulatory elements. Interestingly, no sgRNA targeting the 5’ J region was identified that influenced TRA expression. In contrast, several sgRNAs targeting enhancer alpha element Tα2, were identified that compromised the expression of the TCRα chain in Jurkat E6.1, as well as in a subset of human primary T cells. Our results provide new insights into the regulation of TRA in human peripheral T cells, advancing our understanding of how constitutive TRA expression is driven and regulated.